1989
DOI: 10.1017/s0022149x00008877
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of infective larvae of bovine gastrointestinal trichostrongylids in dry season contaminated pastures in the Nigerian derived savanna

Abstract: Five experimental grass paddocks were sequentially contaminated with fresh bovine faeces containing known numbers of eggs of predominantly Haemonchus and Cooperia spp. during the 1984/85 dry season (November to March). Faecal, herbage and soil samples were examined at regular intervals between November and June in order to determine the rate of development and mortality of infective larvae (L3) in faeces, the pattern of herbage infestation with L3 and the role of faeces and soil as reservoirs of L3 during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…present in the dung of cattle it has been shown that, once development is completed, L3 cannot escape once dung becomes desiccated (Williams and Bilkovich, 1973;Chiejina and Fakae, 1989;Agyei, 1997;Silva et al 2008). For Ostertagia, Haemonchus and Cooperia spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…present in the dung of cattle it has been shown that, once development is completed, L3 cannot escape once dung becomes desiccated (Williams and Bilkovich, 1973;Chiejina and Fakae, 1989;Agyei, 1997;Silva et al 2008). For Ostertagia, Haemonchus and Cooperia spp.…”
Section: Introductionmentioning
confidence: 99%
“…For Ostertagia, Haemonchus and Cooperia spp. present in the dung of cattle it has been shown that, once development is completed, L3 cannot escape once dung becomes desiccated (Williams and Bilkovich, 1973; Chiejina and Fakae, 1989; Agyei, 1997; Silva et al 2008). On dry, warm, days, cattle faeces, which are normally more liquid than sheep faeces and dropped in pats rather than in pellets, rapidly form a crust on the pat surface.…”
Section: Introductionmentioning
confidence: 99%
“…Na Nigéria, fezes de caprinos sofrem completa desidratação em 24 horas, na estação seca, e em 3 a 4 dias na estação chuvosa (Chiejina & Fakae, 1989). Tendo-se em vista a rápida dessecação das fezes de pequenos ruminantes, o período de maior disponibilidade de formas infectantes na pastagem é a época chuvosa.…”
Section: Resultsunclassified
“…Así mismo, en otro estudio dirigido a determinar la supervivencia de larvas de nematodos de vacas en una época seca de Australia, se observó que los mayores picos de larvas infectivas ocurrieron en épocas de lluvia, épocas precedidas de intensa sequía, porque, probablemente, el estiércol seco sirve de reservorio de larvas en épocas secas, y la reanudación de las lluvias favorece su traslación a los pastos (Barger, 1984). La misma observación fue reportada en los resultados de una investigación llevada a cabo en Nigeria (Chiejina, 1989). De esta manera, fue explicado un extenso brote de gastroenteritis parasitaria ocurrido en Australia en 1960, precedido de una época seca, donde el invierno desencadenó el incremento de larvas infectivas en las praderas.…”
Section: Epidemiología De Las Larvas Infectantes De Los Nematodos Gasunclassified